Réflexions juridiques sur l’articulation entre biodiversité et planification de l’espace maritime en contexte transfrontalier – illustration franco-belge - Betty Queffelec (Développement Durable et Territoires)
From a geographical and material point of view, biodiversity is transboundary. It links conservation, exploitation and research. As a result, integrating biodiversity to Maritime Spatial Planning (MSP) is complex but useful. Indeed, this process links sea uses as well as public policies at sea. It aims to implement an ecosystem approach. This transboundary and integrated approach is especially suitable for biodiversity. But its implementation is tricky. In practice, MSP is mainly developed at national level and bilateral cooperation between two States like France and Belgium still remains broadly sectorial. Integration between conservation and exploitation of biodiversity can be complex especially in a cross-border zone. Implementation of Natura 2000 and Common Fisheries Policy can show it. That’s why MSP keeps an interesting potential to allow developing a more integrated cooperation.